PENEGAKAN HUKUM KEPADA WARGA NEGARA ASING TERKAIT TINDAK PIDANA KEIMIGRASIAN DOKUMEN PALSU - Dimas Refaldy; Tri Sulistyowati; Refaldy, Dimas (Faculty of Law, Universitas Trisakti, 2023)
Indonesian Immigration is regulated by Law no. 6 of 2011 concerning Immigration, which is carried out by the Directorate General of Immigration in accordance with Article 1 paragraph (6). Problems: how did the violation of the use of fake immigration documents by Muhammad Habib a Bangladesh citizen occur and how was the supervision of foreigners who used fake documents in Indonesia, and was the District Court Decision Number: 172/Pid.B/2020/Pn.Tsm against Muhammad Habib is in accordance with the law on Immigration. This research is normative, descriptive in nature, uses secondary data, analyzed qualitatively, conclusions are drawn using a deductive method. Research results: Muhammad Habib made a mistake by submitting fake identity documents. Supervision of foreigners is carried out in accordance with a selective policy which aims to ensure that foreign nationals come to Indonesia to bring benefits to Indonesia.